A coupled biodynamic model for crowd-footbridge interaction. (15th December 2018) - Toso, Marcelo André; Gomes, Herbert Martins
Highlights: A new biodynamic synchronized coupled model for walking pedestrians is proposed. Simulations accounts for pedestrian's kinetic and kinematic measured walking parameters. Experimental data for accelerations on a footbridge crossed by different crowd densities are compared. Frequency and damping structural modifications are captured by the new model. The simulation results are in good agreement with the experimental measurements. Abstract: Nowadays, there are growing interests in vibration serviceability assessments of high buildings, slabs, metallic and timber structures, and composite footbridges. Indeed, new design trends of composite footbridges make them slender civil structures that may be affected by the load action of walking pedestrians resulting in large deflections or even uncomfortable vibrations. Furthermore, the presence of people on the footbridges cause the addition of mass to the structural system and due to the human bodýs ability to absorb vibrational energy, an increase in structural damping. In this paper, the interaction between pedestrian and structure is modelled using data from pedestrian characteristics and vibration data from a measured footbridge as a comparison basis. The novelty of the papers relies on the proposed new Biodynamic Synchronized Coupled Model (BSCM). It consists in a fully synchronized force model in the longitudinal and lateral direction of pedestrian's movement and a biodynamic model (with parameters mass, damping and stiffness). This model is coupled to the structural FEM at the feet's contact points. Pedestrians are treated as individuals with intrinsic kinetic and kinematic parameters following a measured correlation matrix obtained by the use of an especially designed force platform. Finally, the adequacy of the proposed model to represent the pedestrians as BSCM for the walking effects on the structure is investigated by experimentally measured vertical accelerations on a footbridge where two crowd densities, freely walking and synchronism of the pacing rate with continuous crossing are also investigated.